Evaluasi Program Pengurangan Resiko Bencana Terpadu Berbasis Masyarakat - Nur Khanif; Bambang Suteng Sulasmono; Bambang Ismanto (Universitas Kristen Satya Wacana, 2021)
This study evaluated the Program of Disaster Risk Reduction (DRR) at SMP Negeri 1 Selo. This type of research was evaluative research with CIPP model which conducted based on Context, Input, Process and Product in the implementation of DRR Program. Data collection techniques were done using interviews, observation, and document study. Data analysis in this study included data collection, data reduction, data display and verification. This study used triangulation to validate the datas. The results showed: (1) in the Context of evaluation, the DRR Education Program at SMP Negeri 1 Selo is categorized as good, because it is in accordance with the needs of the school. The school is not only getting support from outside parties, but also having clear goals, backgrounds, and requirements for organizing. (2) In evaluating Input, this program answers the needs of school. The number of human resources involved and competent is sufficient. Facilities and infrastructure as well as funds are also adequate. The mechanism that the school has is clear and detailed. Program input is considered good. (3) In the Process, most activities (3-5 activities) can be carried out well. Human resources are fulfilled and functioning. Funding is available but inefficient and there is a lack of infrastructure. In general, the implementation has followed the mechanism. The DRR process at SMP Negeri 1 Selo is considered reasonable, (4) In the Product, most of the activities in DRR Program were achieved, the knowledge and the skills of school members were significantly improved but the attitude/concern of school members to disasters had not increased significantly and it had a considerable impact. Thus, the products were considered fair. Based on the results of the research, sustainability policy can be taken. The program should be continued with improvements of mechanism especially in the form of scheduling and plan of program sustainability and improvement of infrastructure facilities.